2018
DOI: 10.1089/dna.2018.4376
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Haplotypes of theABCB1Gene Encoding the P-Glycoprotein Differentially Affect Its Promoter Activity by Altering Transcription Factor Binding

Abstract: Promoter single nucleotide polymorphisms (SNPs) of the ABCB1 gene, encoding the placental efflux transporter P-glycoprotein, can alter its expression and affect fetal exposure to therapeutics and environmental xenobiotics. SNPs are not arrayed as independent variants but as combinations forming defined haplotypes. Recently, we defined the haplotypes encompassing ABCB1 promoter SNPs and found that ABCB1 haplotypes differentially affect its promoter activity. The mechanism(s) by which ABCB1 haplotypes alter its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These results provide an important reference for the molecular mechanism of transcriptional regulation of KLF7 in chicken adipose tissue ( Lin et al, 2021 ). Promoter haplotypes of ABCB1 encoding P-glycoprotein differentially affect its promoter activity by altering transcription factor binding ( Speidel et al, 2018 ). By constructing pGL3-T, pGL3-C, and pGL3-Basic for dual luciferase reporting assays, we found that MC1R g.18838624 T > C polymorphism significantly regulated the activity of the MC1R promoter, and the promoter activity in the CC genotype was significantly higher than that in the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide an important reference for the molecular mechanism of transcriptional regulation of KLF7 in chicken adipose tissue ( Lin et al, 2021 ). Promoter haplotypes of ABCB1 encoding P-glycoprotein differentially affect its promoter activity by altering transcription factor binding ( Speidel et al, 2018 ). By constructing pGL3-T, pGL3-C, and pGL3-Basic for dual luciferase reporting assays, we found that MC1R g.18838624 T > C polymorphism significantly regulated the activity of the MC1R promoter, and the promoter activity in the CC genotype was significantly higher than that in the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Because SNPs do not occur in isolation of each other, but rather as combinations forming defined haplotypes, the phenotypic effect of individual SNPs is not always consistent with functional effects. Thus, genotyping single or a few individual SNPs may fail to reflect the true functionality of genetic variants [ 48 ]. Therefore, it should be recommended that future studies evaluate haplotypes to establish the functional effects that a collection of SNPs may have on response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2018) found that polymorphisms of the HOMER1 gene are associated with piglet splay leg syndrome and the G allele of rs325197091 (A > G) may create a new binding site of transcription factor ARNT, which could enhance HOMER1 promoter activity and expression. Promoter haplotypes of the ABCB1 gene encoding the P-glycoprotein differentially affects its promoter activity by altering the transcription factor binding (Speidel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%